Model Evaluasi Pembelajaran Berbasis HOTS (Higher Order Thinking Skills): Studi Literatur Sistematis - Milla, Daindo; I Gede Ratnaya; I Gusti Lanang Agung Parwata; I Dewa Ayu Made Budhyan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The growing demand for students to think critically, creatively, and solve complex problems highlights the importance of assessment models based on Higher Order Thinking Skills (HOTS). However, implementing evaluation models that genuinely promote higher-level thinking skills remains challenging, particularly in designing and applying appropriate instruments in the classroom. This study aims to systematically review various HOTS-oriented assessment models within primary and secondary education contexts. A systematic literature review was conducted on scientific articles published between 2015 and 2024. The findings indicate that HOTS-based evaluation models commonly integrate performance assessments, projects, case studies, and open-ended questions that require analysis and synthesis. The study also reveals that the successful implementation of HOTS assessment models is strongly influenced by teachers’ competencies, curriculum support, and the use of appropriate scoring rubrics. These findings imply the need for ongoing professional development for educators to effectively design and implement assessment models aligned with the development of higher-order thinking skills in a contextual and sustainable manner